Infusing the new technologies debate with a socio-economic agenda. Issue 2 (1st September 2014) - Wilson, Bruce
Abstract : Dramatic changes occurred in the international economy in the latter part of the twentieth century. CERI, the Centre for Education Research and Innovation at the OECD, was an important contributor to the understanding of the nature and implications of these developments, and in foreshadowing the central policy challenges which would arise. Jarl Bengtsson was an important catalyst in focusing CERI's attention on these issues, particularly in relation to their implications for education, both in formal institutional learning and also the less immediate yet profound world of work. In the latter realm, he made a particular contribution which has remained rather hidden as part of the broader OECD work on new technologies and their implications, particularly for employment. This article reviews the thinking on ICT, people, work and education before returning to CERI's specific contribution.